2020
DOI: 10.15406/mojes.2020.05.00179
|View full text |Cite
|
Sign up to set email alerts
|

Agro morphological Characterization and Evaluation of Okra [Abelmoschus esculentus (L.) Moench] Genotypes for Yield and Other Variability Components at Melkassa, Central Ethiopia

Abstract: Okra [Abelmoschus esculentus (L).Moench] is one of indigenous and endemic genetic resource of Ethiopia as well as Benishangul Gumuz, but only few studies were carried out to assess its diversity and performance throughout the country and specifically no research conducted to assess diversity of okra within regional state. Therefore, this study was conducted with the objective of assess the genetic divergence and estimate the genetic variability components in okra genotypes collected from regional state. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…e short picking interval encouraged the plant to produce higher number of fruits per plant and long picking interval increased the fruit size and weight [27]. e present result is in agreement with two reports from Ethiopia [21,22,28]. A similar result had also been reported from India [29,30].…”
Section: Fruit Yield and Yield Componentssupporting
confidence: 92%
See 1 more Smart Citation
“…e short picking interval encouraged the plant to produce higher number of fruits per plant and long picking interval increased the fruit size and weight [27]. e present result is in agreement with two reports from Ethiopia [21,22,28]. A similar result had also been reported from India [29,30].…”
Section: Fruit Yield and Yield Componentssupporting
confidence: 92%
“…e results of the analysis of variance for 13 phenology and growth traits indicated the presence of significant differences among the 36 okra genotypes, and genotypes had nonsignificant difference for number of flower epicalyxes. Reference [21] also characterized okra genotypes collected from Benishangul-Gumuz reginal state of Ethiopia and reported that there were no significant differences in numbers of flower epicalyxes among the studied genotypes.…”
Section: Phenology and Growth Traitsmentioning
confidence: 99%
“…This is in tandem with studies by Temam et al . [ 35 ] who reported differences in stem girths of various okra cultivars ranging from 14.5–30.5 cm in Ethiopia. These results contradict the findings of Azeem et al ., [ 36 ] who reported an insignificant difference in stem girth among the various okra cultivars under his study.…”
Section: Discussionmentioning
confidence: 99%
“…Heritability determines the degree of phenotypic variation caused by additive gene activity. Heritability is a valuable indication of how well traits are handed down from parents to their offspring (Temam et al, 2020). The proportion of heritable variation impacts the consistency of progeny performance in following genera-tions.…”
Section: Heritability and Genetic Advancementioning
confidence: 99%
“…Table 3 and Fig programmes of sesame development for characteristics such as seed length and seed yield per plant will be implemented in the future. Backcrossing is essential to concentrate these traits in genotypes since many traits seem to be governed by alleles with additive effects (Temam et al, 2020). For seed thickness to No.…”
Section: Heritability and Genetic Advancementioning
confidence: 99%